LO16: Safety and efficiency of emergency physician supplementation in a provincially nurse-staffed telephone service for urgent caller advice. (15th May 2017) - Grafstein, E.; Abu-Laban, R.B.; Wong, B.; Stenstrom, R.; Scheuermeyer, F.X.; Root, M.; Doan, Q.
Abstract : Introduction: In 2008 British Columbia created a nurse (RN) staffed telephone triage service, (TTS) to provide timely advice to non-911 callers (811). A perception exists that some callers are inappropriately directed to emergency departments (EDs) thereby worsening crowding. We sought to determine whether supplementary emergency physician (EP) triage would decrease ED visits while preserving caller safety and satisfaction.Methods: TTS RNs use computer algorithms and judgment to triage callers. Potentially sick callers are directed to "seek care now" (red calls). Often this is to an ED depending on acuity and time of day. In the Vancouver Health Region from April-September 2016 between 8:00-24:00 hours, a co-located EP also spoke with "red" callers to provide further guidance. Callers were followed up with 1 week and satisfaction was evaluated on a 5-point Likert scale. The TTS data was linked to the regional ED database to assess ED attendance within 7 days, and the provincial vital statistics database for 30-day mortality. Our primary outcome was the proportion of unique "red" callers who did not attend the ED compared with a historical cohort one year earlier without EP triage in place. Secondary outcomes were the proportion of "red" callers advised not to attend the ED but (a) attended, (b) admitted, or (c) died.Results: In the study period there were 5105 "red" calls of which 3440 were transferred to the EP (67.4%), 2958 of EP assessed callers (86.0%) had a family doctor, but only one-quarter of such patients could contact their family doctor. Overall, 2301/3440 "red" callers did not attend an ED (67.0%) compared to 2508/4770 in the control period (52.6%), for an absolute reduction of 14.4% (95% CI 12.2 to 16.4%, p<0.0001). In callers for those <17 years old there was a 20.3% (95% CI 16.5 to 24.1%) reduction in ED visits compared to the control group: 771/1520 (50.7%) vs 364/1067 (30.4%). 40% of callers attending an ED (458/1139) were advised to try non-ED follow up by the MD and 108 (9.5%) were admitted, with no difference in 30-day mortality between groups. Age and CTAS distribution were similar between the two groups and the non MD-transferred cohort. Mean caller satisfaction was excellent (4.7/5.0).Conclusion: EP supplementation of a RN advice service has the potential to reduce ED visits by almost 15% while providing excellent safety and satisfaction.